Muestra pictórica. Riqueza de la producción del cantón Machala, utilizando la técnica del óleo - Romero León, Andrés Francisco (2012)
To shape the pictorial exhibition, sketches in the back were depicted in works of art Oil where he represented the agricultural sector of the city of Machala, especially the banana, shrimp, artisanal fisheries were used, thus demonstrating the high level of entrepreneurship and professionalism that were obtained in university classrooms